EVALUATION OF THE OUTCOMES OF RENAL STONE MANAGEMENT BY FLEXIBLE RETROGRADE INTRARENAL SURGERY WITHOUT PREOPERATIVE URETERAL STENTING - Truong Thanh Tung,; Le Quang Anh,; Le Quang Hai, (Tạp chí Y học Quân sự, 2026)
Objective: Evaluation of the results of renal stone treatment by retrograde intrarenal surgery using flexible endoscopy without preoperative ureteral stenting. Subject and methods: An interventional study with retrospective and prospective descriptive design, including 232 patients, who had indications for and underwent retrograde intrarenal surgery using flexible endoscopy without preoperative ureteral stenting at Thanh Hoa Provincial General Hospital from January 2025 to January 2026. Results: The mean age of patients was 49.8 ± 12.6 years. The mean renal stone size was 12.39 ± 4.97 mm. The rates of isolated lower calyceal stones and isolated renal pelvic stones were 24.1% and 34.5%, respectively. The mean operative time was 45.40 ± 11.63 minutes. The mean lithotripsy time was 33.75 ± 10.06 minutes. The mean postoperative hospital stay was 3.43 ± 1.70 days. The stone-free rate was 77.2% immediately after surgery, 85.3% at 1 month postoperatively, 86.6% at 3 months postoperatively. Conclusions: Retrograde intrarenal surgery using flexible endoscopy without preoperative ureteral stenting is an effective, safe treatment method for renal stones, with a low complication rate and reduced hospital stay.